Calibration of strain gage instrumentation for an aircraft pylon - Tan, Alan Dao Yang (2011)
This final year project developed a load calibration strain gage procedure and system for a F16 non-jettisonable fuel pylon with an existing fixture. The system identified the best strain gage bridge for load calibration. Most importantly, the substitutes for the best strain gage bridges were identified, which becomes a solution for a damaged strain gage bridge as the next best strain gage bridge that can be used for load calibration.